Cell cycle-dependent changes in the organization of an intermediate filament-associated protein: correlation with phosphorylation by p34cdc2. - Skalli, O (1992)
During mitosis in BHK-21 baby hamster kidney cells the hyperphosphorylation of the type III intermediate filament (IF) protein vimentin is accompanied by the disruption of the IF network into punctate, protofilamentous structures. In this study, the morphological and biochemical changes of IFAP 300, a 300-kDa IF-crossbridging protein, are examined during mitosis. Double-label immunofluorescence shows that the distribution of IFAP 300 coincides with the typical filamentous pattern displayed by vimentin in interphase cells, whereas in mitotic cells it is reorganized into a punctate, nonfilamentous pattern. Accompanying these latter morphological changes, IFAP 300 is phosphorylated at a unique, mitosis-specific site. Comparison of the sites phosphorylated in cultured cells with those phosphorylated in vitro by various kinases suggests that IFAP 300 is phosphorylated by the same two kinases that phosphorylate vimentin during mitosis. One of these is p34cdc2 protein kinase, which appears to be responsible for the phosphorylation of the mitosis-specific site. The other kinase phosphorylates IFAP 300 in vitro at a site that is also found in the protein immunoprecipitated from either mitotic or interphase cells. In contrast to vimentin, the phosphorylation levels of IFAP 300 are not obviously altered between interphase and mitosis. Our results show that IFAP 300 is a physiological substrate for p34cdc2 and that this kinase may be involved in the mitotic reorganization of IFAP 300 by phosphorylating a mitosis-specific site. Taken together with our previous results, this study suggests that the activation of p34cdc2 coordinates the mitotic reorganization of the vimentin IF network both by severing IF-IF connections mediated by IFAP 300 and by disassembling individual IFs into protofilaments.